Exploring management strategies for Private Islamic Schools in the deep south of Thailand using the PMDG guidelines: An application of Fuzzy Delphi method - Lateh, Afifi; Thongsuk, Jarunee; Machae, Daniya; Masae, Abdunkareem; Lateh, Alawee; Khongpheng, Narida; Pooteh, Rohani (Edelweiss Applied Science and Technology, 2024)
Developing educational institution strategies empowers them to capitalize on strengths and opportunities, addressing gaps for advancement. Private Islamic schools in southern Thailand, nearly 500 in number, can enhance their performance by adopting management strategies inspired by the successful Pondok Modern Darussalam Gontor (PMDG) boarding school model. This study aims to develop such strategies and activities for these schools, guided by PMDG principles and selected through the Fuzzy Delphi method. The study employed mixed methods research with an exploratory sequential design. It began by formulating strategies based on PMDG guidelines, followed by expert-led discussions involving 10 individuals. Activities were then developed for each strategy, deliberated upon in a workshop with 89 participants. Strategies and activities were presented to expert groups and PMDG faculty, comprising 21 individuals. Finally, the Fuzzy Delphi method was used to select the top three activities for each strategy, with input from 18 experts. The research produced 12 strategies and 79 activities, with 36 emerging as top choices. These strategies and activities aim to empower private schools to provide Islamic education, not only in Thailand but also internationally. Their adaptability ensures they align with the unique context of each school and its surroundings.